2018
DOI: 10.1103/physreve.98.042129
|View full text |Cite
|
Sign up to set email alerts
|

Fickian yet non-Gaussian diffusion is not ubiquitous in soft matter

Abstract: Recent studies unveiled the Fickian yet non-Gaussian (FNG) dynamics of many soft matter systems and suggested this phenomenon as a general characteristic of the diffusion in complex fluids. In particular, it was shown that the distribution of particle displacements in Fickian diffusion is not necessarily Gaussian, and thus the Einstein and Smoluchowski theory describing the Brownian motion of individual objects in a fluid would not be applicable. In this Letter, we investigate whether the FNG dynamics so far r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…By definition, the self-dual shape is an intermediate geometry between prolate and oblate, where length (L), width (W ) and thickness (T ) are such that W = √ LT . Our simulations also confirmed the occurrence of a Fickian and Gaussian dynamics at both short and long times, thus providing an alternative picture to the claimed universality of Fickian yet non-Gaussian dynamics in soft-matter systems 41 . For its potential impact in nanotechnology, equally intriguing is the outof-equilibrium dynamics of cuboids, especially because it can spark phase switching and new material properties.…”
Section: Introductionsupporting
confidence: 72%
“…By definition, the self-dual shape is an intermediate geometry between prolate and oblate, where length (L), width (W ) and thickness (T ) are such that W = √ LT . Our simulations also confirmed the occurrence of a Fickian and Gaussian dynamics at both short and long times, thus providing an alternative picture to the claimed universality of Fickian yet non-Gaussian dynamics in soft-matter systems 41 . For its potential impact in nanotechnology, equally intriguing is the outof-equilibrium dynamics of cuboids, especially because it can spark phase switching and new material properties.…”
Section: Introductionsupporting
confidence: 72%
“…For geometrical reasons, diffusion anisotropy becomes irrelevant in perfectly regular cubic lattices. One expects that any bias favouring displacements tangent to the available paths should become noticeable, either when dealing with anisotropic tracers or particles, 50 or in random networks with fractal paths, 40 which is the present case. Here we find that this effect is more significant in porous media where obstacle walls are thicker (as in the colloidal gel) because normal and tangent directions are more clearly differentiated (see Fig.…”
Section: Discussionmentioning
confidence: 85%
“…For a system of identical particles royalsocietypublishing.org/journal/rsfs Interface Focus 9: 20180074 obeying the diffusion equation or in the ballistic regime with a velocity given by the Maxwell-Boltzmann distribution, the mean squared displacement of each particle increases linearly with time and the self-part of the van Hove self-correlation function has a Gaussian shape. In many soft matter systems however, it has been shown that the Gaussian approximation is not valid and that particles move either slower or faster than theoretically predicted [38][39][40]. We calculated G(r,Dt) for different time intervals Dt between 2.4 and 12t.…”
Section: Resultsmentioning
confidence: 99%